HARAPAN DIGITAL NATIVE TERHADAP PERPUSTAKAAN MASA DEPAN PADA PERGURUAN TINGGI - ANTON HERMAWAN (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2020)
In the last ten years the development of information technology is so fast, this is marked by the increasingly sophisticated communication devices and the increasing use of applications. The generation that was born at the start of the transition of technology is certainly a generation that is